Itu PENGARUH SISTEM PENGUKURAN KINERJA TERHADAP PEMBERDAYAAN PSIKOLOGI DAN KINERJA KARYAWAN (Studi pada PT. Bank Bukopin Bandar Lampung): Bahasa Indonesia - Eka Travilta Oktaria (Universitas Putera Batam, 2020)
This research aims to examine how the effects of the performance measurement on psychological empowerment and employee performance. In order to attain the aim of the study, this research is conducted the banking sector, especially Bank Bukopin of Bandar Lampung. According to 40 respondent, researchers analyzed data using the Structural Equation Modelling (SEM) in particularly smart PLS. The result of the study show that the first hypothesis of performance measurement has positive and statistically significant on psychological empowerment hypothesis 1 is supported. However, the second hypothesis is partially supported psychological empowerment on employee performance, and the third hypothesis performance measurement results positive influence on employee performance, then the third hypothesis is supported. This study implies that performance measurement enables to improve employee performance both direct and indirectly through psychological empowerment.